Approaches to indices choice and the experience of assessment of soil covering ability to realize general biospheric functions (analytical review) - V. I. Titova (Аграрная наука Евро-Северо-Востока, 2018)
The analysis of scientific papers concerning economic significance of evaluation of agricultural land fertility and quality has been done. This analysis was made according to technological and cost parameters. It is noted that the study of soil ability to realize the general biospheric functions is of current importance now not only in theoretical but also in practical aspect. This research is required by state environmental agencies when they execute their oversight functions. It is also very important for land owners when they organize a land rent or title transfer on the stage of ecological and economic evaluation of agricultural land. The data on the content of organic substance and basic plant food compounds in the soil are proposed as criterions for assessment the soil ability to realize general biospheric functions. The economic evaluation of soil general biospheric functions support may be done by analyzing the increase of humus, mobile potassium and labile phosphorus for a certain period of time as well as by costs for applying organic fertilizers (manure) and mineral fertilizers (superphosphate and potassium chloride) to provide the increase. The costs for support of soil fertility (an environment component and a guarantor of biogeocenotic functions execution) was calculated and it was 2 259.5 rubles a year per hectare. The podzolic chernozem soil of one farm in Nizhny Novgorod region was taken as an example for this assessment.